2008
DOI: 10.1002/chem.200701330
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Specific Internalization Study of an Aptamer from Whole Cell Selection

Abstract: Nucleic acid aptamers have been shown many unique applications as excellent probes in molecular recognition. However, few examples are reported which show that aptamers can be internalized inside living cells for aptamer functional studies and for targeted intracellular delivery. This is mainly due to the limited number of aptamers available for cell-specific recognition, and the lack of research on their extra- and intracellular functions. One of the major difficulties in aptamers' in vivo application is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(187 citation statements)
references
References 32 publications
9
178
0
Order By: Relevance
“…For efficient drug transport, it is essential that macromolecular drug transporters be internalized by diseased cells. Previous work showed that sgc8 was specifically internalized by target CEM cells via endocytosis (35). Compared with the results of a study using sgc8-NTrs at 4°C (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…For efficient drug transport, it is essential that macromolecular drug transporters be internalized by diseased cells. Previous work showed that sgc8 was specifically internalized by target CEM cells via endocytosis (35). Compared with the results of a study using sgc8-NTrs at 4°C (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Cells were treated with free Dox, as a control, or Dox transported by sgc8-NTrs, respectively, followed by microscopic examination. In addition, transferrin-Alexa 633 was used to locate the endosomes (35). The recovery of Dox fluorescence (fluorescence "ON") after release from nanotrains enabled the real-time signaling of intracellular drug unloading.…”
Section: Resultsmentioning
confidence: 99%
“…The sgc8 aptamer, from which sgc8c is derived is known to be taken into cells via receptor mediated endocytosis [22]. Computer modelling.…”
Section: Aptamer Structurementioning
confidence: 99%
“…Direct imaging of protein colocalization (nucleolin and integrin αvβ 3 ) based on FRET has also been reported (Kang et al, 2009b). In addition to cellular localization, fluorescence labeled aptamers have been used to study protein trafficking including endocytosis of human protein kinase-7 (PTK7) from membrane into endosome (Xiao et al, 2008) and endocytosis of angiogenin into cytoplasm and nuclei as scattered spots (Li et al, 2008). Particularly, protein trafficking dynamics has been imaged and quantified in real-time in living cells by an aptamer probe.…”
Section: Protein Localization and Trafficking In Cells By Aptamer Imamentioning
confidence: 99%